Fights for Education: proposals for education funding in the ‘Pioneers of New Education Manifesto’ - Daniel Santos Braga (Fineduca, 2018)
The article aims to identify the proposals of organization of education funding in Brazil in the 1932 document entitled Pioneers of New Education Manifesto and to analyze such proposals in relation to the political and social context of the period in which it was written. The historical text, thought as a document/monument, reveals that the directions of Brazilian education and society were in dispute, and that the intention of the authors was precisely to present a societal project. It was concluded that, although the manifesto did not elicit the desired transformations at the time of writing, it inspired the models of organization of the public funding of contemporary Brazilian education.